Effect of Some Storage Conditions upon the Survival of Some Fungal Spores - A. Al-Shikli, Raghad; A.Abdulrasool, Alaa; M. Al-Hiti, Mustafa (Iraqi Journal of Pharmaceutical Sciences, 2017)
Folic acid and multivitamin tablets containing Aspergillus flavus Penicillia spp. and Cladosporia spores were prepared at a compression pressure of 148 MN/m2 and stored at 35Â°C under different relative humidifies (75,85, and 95)% within air tight containers, to study the effect of storage condition on them, as well as ,the estimation of the microbial level of the raw materials intended to be used in the two kinds of tablets . Result showed that some raw materials derived from natural origin were heavily contaminated with microorganism compared to that of synthetic origin ,the results also indicated the effect of relative humidity , types of fungal spore , and the hygroscopic nature of exicpient upon survival. Multivitamin tablets showed more survival than folic acid tablets and this is due to the presence of more nutrients. No aflatoxin was obtained from both multivitamin and folic tablets at 35Â°C temperature; this is due to the temperature which is not an optimum temperature for aflatoxin B1 production.Key words: Storage conditions of tablet, fungal spores